(untitled) (Research, Society and Development, 2020)
The growing demand of the consumer market for healthier products and services that are free from contaminants has aroused interest in scientific research. Fruit bagging is one of the oldest and most efficient phytosanitary practices, in turn, there are few studies related to the coloring of the material used for tomato cultivation. The objective of this study was to evaluate the practice of bagging tomato fruits of the hybrid Compack under different colors of Non-Woven Fabric in relation to the chemical, physical and productive characteristics of the fruits, as well as the visual damage index presented, totalizing 20 analyzed parameters. The experiment was carried out in the city of Goiânia, Goiás, Brazil. The tested treatments were: T1- fruits bagged with red TNT, T2- fruits bagged with blue TNT, T3- fruits bagged with yellow TNT, T4- fruits bagged with white TNT and T5- fruits without bagging. The T1 and T4 showed better averages for pH, AT and SS / AT ratio, in addition to conserving the average values of mass. The other chemical parameters (vitamin C, soluble solid), physical (length and firmness), colorimetric (luminosity and chromaticity) did not show any significant difference. The results obtained for °Hue indicated the T1 as a more reddish skin color. The production indexes evaluated, as well as the average number of fruits with the presence of damage, did not show any significant difference. The T2 showed the lowest mean values productive. The practice of bagging also showed a reduction in the average damage values by Septoria lycopersici and Alternaria solani.